PENGARUH KOLABORASI DOSEN, KEMAMPUAN TEKNIS DOSEN, DAN PARTISIPASI DARING DOSEN TERHADAP KEPUASAN MAHASISWA PADA PROGRAM PENDIDIKAN JARAK JAUH DI UNIVERSITAS XYZ [THE INFLUENCE OF LECTURER COLLABORATION, LECTURER TECHNICAL ABILITY, AND LECTURER ONLINE PARTICIPATION ON STUDENT SATISFACTION IN DISTANCE EDUCATION PROGRAMS AT XYZ UNIVERSITY] - Bawono, Masatyo; Yugopuspito, Pujianto (Polyglot, 2024)
AbstractStudent satisfaction is one of the factors that influence student motivation and learning process. The more satisfied students are, the higher their motivation to complete their studies and have a better learning process. This study aims to see the effect of lecturers' collaboration level, lecturers' technical ability, and lecturers' online participation in the online classroom on student satisfaction. The research was conducted on active students of the Communication Science Distance Education study program in 2018 with a total of 88 respondents. Data were obtained through a survey consisting of 40 questions. The data were processed with the PLS method using SmartPLS software. The results obtained are lecturer collaboration, lecturer technical ability, and lecturer online participation in online classrooms have a positive effect on student satisfaction, with lecturer technical ability being the most influential factor on student satisfaction. Mastery of technology and the use of various methods of lecturer participation in online classrooms are recommended approaches for lecturers to take. Bahasa Indonesia AbstrakKepuasan Mahasiswa merupakan salah satu faktor yang mempengaruhi motivasi dan proses belajar siswa. Semakin puas siswa, maka motivasi mereka semakin tinggi untuk menyelesaikan studi dan memiliki proses belajar yang lebih baik. Penelitian ini bertujuan untuk melihat pengaruh dari tingkat Kolaborasi Dosen, Kemampuan Teknis Dosen, dan Partisipasi Daring Dosen pada online classroom terhadap Kepuasan Mahasiswa. Penelitian dilakukan pada mahasiswa aktif program studi Pendidikan Jarak Jauh Ilmu Komunikasi di tahun 2018 dengan total responden sebanyak 88 orang. Data diperoleh melalui survey yang terdiri dari 40 pertanyaan. Data diolah dengan metode PLS menggunakan perangkat lunak SmartPLS. Hasil yang diperoleh adalah Kolaborasi Dosen, Kemampuan Teknis Dosen, dan Partisipasi Daring Dosen pada ruang kelas daring berpengaruh positif terhadap Kepuasan Mahasiswa, dengan Kemampuan Teknis Dosen yang menjadi faktor paling berpengaruh terhadap kepuasan siswa. Penelitian ini terbatas pada satu program studi saja, dan terbatas pada siswa yang aktif di tahun 2018.